2022
DOI: 10.3389/fnut.2022.866233
|View full text |Cite
|
Sign up to set email alerts
|

Activating Effects of the Bioactive Compounds From Coffee By-Products on FGF21 Signaling Modulate Hepatic Mitochondrial Bioenergetics and Energy Metabolism in vitro

Abstract: Coffee by-products contain bioactive compounds that have been shown to have the capacity to modulate human metabolism. The goal of this study was to investigate the effects of the main bioactive compounds in coffee by-products and two aqueous extracts from the coffee husk and silverskin on the activation of fibroblast growth factor 21 (FGF21) signaling and the subsequent regulation of mitochondrial bioenergetics and lipid and glucose metabolism. HepG2 cells treated with palmitic acid (PA) were used in a non-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 88 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…[ 96 ] In “in vitro” models, treatments with coffee and its derived bioactive compounds it increased the signaling of the batokine FGF21, improving glucose uptake and increasing beta‐oxidation and mitochondrial bioenergetics, contributing to a healthy metabolic profile. [ 97 ] Diet‐induced obese mice that received coffee daily at a concentration of 1% w/w rich in chlorogenic acids and caffeine (571.9 and 653.1 mg kg −1 of diet respectively) for 10 weeks, showed a reduction in body mass and EI and an increase in EE. In BAT, coffee bypassed the whitening, restoring its multilocularity in the high‐fat diet (HFD) induced obesity model.…”
Section: Bioactivity Compounds In Foods and Bat Activation: A Perspec...mentioning
confidence: 99%
“…[ 96 ] In “in vitro” models, treatments with coffee and its derived bioactive compounds it increased the signaling of the batokine FGF21, improving glucose uptake and increasing beta‐oxidation and mitochondrial bioenergetics, contributing to a healthy metabolic profile. [ 97 ] Diet‐induced obese mice that received coffee daily at a concentration of 1% w/w rich in chlorogenic acids and caffeine (571.9 and 653.1 mg kg −1 of diet respectively) for 10 weeks, showed a reduction in body mass and EI and an increase in EE. In BAT, coffee bypassed the whitening, restoring its multilocularity in the high‐fat diet (HFD) induced obesity model.…”
Section: Bioactivity Compounds In Foods and Bat Activation: A Perspec...mentioning
confidence: 99%
“…Then, they were incubated in EMEM supplemented with 10% FBS in the absence (nontreated cells controls, NT) or presence of FFAs (500 µmol L −1 oleic:palmitic acid, 2:1) conjugated in BSA (1%), and the digested soybean varieties (V1, V3, V9, V17, and V18; 10-1000 µg protein mL −1 ) or simvastatin (0.10-10 µg mL −1 ; 0.24-24 µmol L −1 ). After 24 h treatment, supernatants were collected, centrifuged, and stored at −80 • C until being used as described earlier [29]. Once the half maximal inhibitory concentration (IC 50 ) for cholesterol concentration increase was determined, cells were cultivated in the absence (non-treated cells controls, NT) or presence of FFAs (500 µmol L −1 oleic:palmitic acid, 2:1) and the digested soybean varieties (V1, V3, V9, V17, and V18 at IC 50 s 253, 160, 76, 64, and 146 µg protein mL −1 , respectively) or simvastatin (IC 50 = 160 ng mL −1 ).…”
Section: Cell Model Of Metabolic-associated Fatty Liver Diseasementioning
confidence: 99%
“…Likewise, a recent work suggested that aqueous extracts from coffee silverskin (125 μg/mL) stimulated phosphatidylinositol 3-kinase (PI3K) and AMPK signaling ( 66 ). The effect on insulin and PI3K pathways improved hepatic cell insulin sensitivity ( in vitro ), and diminished lipogenesis and gluconeogenesis ( 67 ). In this regard, ferulic acid, an important metabolite of feruloylquinic acids, has been shown to increase the expression levels of PI3-K and GLUT4, thereby increasing glucose uptake in adipocytes ( 55 ).…”
Section: Effects Of the Main Bioactive Components Of Coffee Silverski...mentioning
confidence: 99%
“…A recent study, using aqueous extract of coffee silverskin on hepatic cells (10 to 500 μg/mL), suggested that bioactive compounds, particularly CGA, may regulate glucose metabolism and prevent the development of NAFLD by preventing hyperglycemia and systemic insulin resistance ( 67 ).…”
Section: Effects Of the Main Bioactive Components Of Coffee Silverski...mentioning
confidence: 99%